Disagreement on foundational principles of biological aging - Gladyshev, Vadim N; Anderson, Benjamin; Barlit, Hanna; Barré, Benjamin; Beck, Samuel; Behrouz, Bahareh; Belsky, Daniel W; Chaix, Amandine; Chamoli, Manish; Chen, Brian H; Cheng, Kaiyang; Chuprin, Jane; et al. (PNAS nexus, 2024)
Abstract To gain insight into how researchers of aging perceive the process they study, we conducted a survey among experts in the field. While highlighting some common features of aging, the survey exposed broad disagreement on the foundational issues. What is aging? What causes it? When does it begin? What constitutes rejuvenation? Not only was there no consensus on these and other core questions, but none of the questions received a majority opinion—even regarding the need for consensus itself. Despite many researchers believing they understand aging, their understanding diverges considerably. Importantly, as different processes are labeled as “aging” by researchers, different experimental approaches are prioritized. The survey shed light on the need to better define which aging processes this field should target and what its goals are. It also allowed us to categorize contemporary views on aging and rejuvenation, revealing critical, yet largely unanswered, questions that appear disconnected from the current research focus. Finally, we discuss ways to address the disagreement, which we hope will ultimately aid progress in the field.